2019
DOI: 10.1186/s12966-019-0871-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of implementing public bicycle share programs on cycling: the International Bikeshare Impacts on Cycling and Collisions Study (IBICCS)

Abstract: BackgroundDespite rapid expansion of public bicycle share programs (PBSP), there are limited evaluations of the population-level impacts of these programs on cycling, leaving uncertainty as to whether these programs lead to net health gains at a population level or attract those that already cycle and are sufficiently physically active. Our objective was to determine whether the implementation of PBSPs increased population-level cycling in cities across the US and Canada.MethodsWe conducted repeat cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Although there is evidence of an association between the presence of bike share programs and increased cycling overall ( 21 , 22 ), our study showed substantial racial and economic inequities in Citi Bike participation. Differences in bike share utilization may reflect deficiencies in the original design of the program, which potentially exclude groups from the possible health benefits of active transportation and contribute to increased disparities of health.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Although there is evidence of an association between the presence of bike share programs and increased cycling overall ( 21 , 22 ), our study showed substantial racial and economic inequities in Citi Bike participation. Differences in bike share utilization may reflect deficiencies in the original design of the program, which potentially exclude groups from the possible health benefits of active transportation and contribute to increased disparities of health.…”
Section: Discussioncontrasting
confidence: 75%
“…Bike share programs represent a novel mechanism by which residents may gain access to cycling in the city. Indeed, bike share programs have been associated with an increase in cycling ( 21 ). A report by the NYC Department of Transportation found that the percentage of people who report cycling has increased in the area served by Citi Bike (NYC’s bike share program), but not outside of it ( 22 ).…”
mentioning
confidence: 99%
“…Specific to our cohort, nearly 40% of the roadways around participants’ residences had higher traffic stress. Station proximity is another important motivator for bikeshare frequency [ 6 , 10 ]. While the Philadelphia bikeshare program service area covers an impressive 20 square kilometers (8 square miles) [ 24 ], 20% of the members in our cohort did not reside close (400 m) to a bikeshare station.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have documented increases in cycling behaviors in cities with bikeshare, with much of the evidence coming from the International Bikeshare Impacts on Cycling and Collisions Study [ 9 ]. For example, Hosford et al [ 10 ], used three years (2012–2014) of the study’s repeated-cross-sectional data from two cities with recently implemented programs (Chicago and New York) and three cities without a bikeshare program at the time of the study (Vancouver, Detroit, Philadelphia). The study found that past-week cycling at follow-up was higher among residents living in cities with newly implemented bikeshare programs over the follow-up period (relative to the baseline period and to residents who did not live within the program’s target area or did not live in a city with bikeshare).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-Essentials version 1.4 (Suurmond, van Rhee, & Hak, 2017) was used to compute the sampleweighted average effect (Hedges g+) of the interventions on cycling, adjusting effect sizes from studies with different methodologies using the procedures described by Morris and DeShon (2002). Three of the studies (Goodman, Panter, Sharp, & Ogilvie, 2013;Hosford et al, 2019;Krizek, Barnes, & Thompson, 2009) had very large samples (i.e., > 3 SD from the average sample size), so we "winsorized" these sample sizes to the next largest one within the "normal" range, so as not to bias the overall effect size.…”
Section: Effect Size Calculation/meta-analytic Strategymentioning
confidence: 99%